2018
DOI: 10.1088/1361-6641/aaed93
|View full text |Cite
|
Sign up to set email alerts
|

Non-polar (11-20) GaN grown on sapphire with double overgrowth on micro-rod/stripe templates

et al.

Abstract: This is a repository copy of Non-polar (11-20) GaN grown on sapphire with double overgrowth on micro-rod/stripe templates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…The slope of the sapphire cones allowed for tilted nucleation of a-plane GaN similar to a-plane growth on r-plane sapphire [ 27 ]. The stacking faults indicated that GaN on the cone sidewalls presented a-plane orientation [ 28 , 29 , 30 , 31 ]. We observed that there were some semi-polar and non-polar planes in sample A, by our calculation from SAED patterns in Figure 7 b.…”
Section: Resultsmentioning
confidence: 99%
“…The slope of the sapphire cones allowed for tilted nucleation of a-plane GaN similar to a-plane growth on r-plane sapphire [ 27 ]. The stacking faults indicated that GaN on the cone sidewalls presented a-plane orientation [ 28 , 29 , 30 , 31 ]. We observed that there were some semi-polar and non-polar planes in sample A, by our calculation from SAED patterns in Figure 7 b.…”
Section: Resultsmentioning
confidence: 99%
“…19 ), forming a mushroom configuration. The specially designed patterning can compensate for the intrinsically anisotropic in-plane growth rate of nonpolar GaN 23 . Consequently, the overgrowth on the template can achieve not only substantially improved crystal quality, but also an atomically flat surface as result of a quick coalescence.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, selective growth using a mask is a good choice, which not only avoids the damage caused by etching, but also has the characteristics of orderly and controllable growth. [ 15–18 ] In this article, the InGaN/AlGaN MQW microrod array structure was grown using the microhole mask, and its structure and luminescence characteristics were analyzed.…”
Section: Introductionmentioning
confidence: 99%